2020
DOI: 10.1109/tit.2019.2934134
|View full text |Cite
|
Sign up to set email alerts
|

Extended Integrated Interleaved Codes Over Any Field With Applications to Locally Recoverable Codes

Abstract: Integrated Interleaved (II) and Extended Integrated Interleaved (EII) codes are a versatile alternative for Locally Recoverable (LRC) codes, since they require fields of relatively small size. II and EII codes are generally defined over Reed-Solomon type of codes. A new comprehensive definition of EII codes is presented, allowing for EII codes over any field, and in particular, over the binary field GF(2). The traditional definition of II and EII codes is shown to be a special case of the new definition. Impro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
51
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(53 citation statements)
references
References 68 publications
(316 reference statements)
1
51
0
Order By: Relevance
“…and GCCs show large potential applications, e.g., in data transmission systems [36] and Flash memory [37], [38]. TPCs and GTPCs exhibit large advantages in magnetic storage systems [39]- [42], Flash memory [43], [44] and in constructing locally repairable codes for distributed storage systems [45]- [47]. In [48], it is shown that Polar codes can be treated as GCCs for a fast encoding.…”
Section: Classical Concatenated Codesmentioning
confidence: 99%
“…and GCCs show large potential applications, e.g., in data transmission systems [36] and Flash memory [37], [38]. TPCs and GTPCs exhibit large advantages in magnetic storage systems [39]- [42], Flash memory [43], [44] and in constructing locally repairable codes for distributed storage systems [45]- [47]. In [48], it is shown that Polar codes can be treated as GCCs for a fast encoding.…”
Section: Classical Concatenated Codesmentioning
confidence: 99%
“…As in the case (r, δ) = (2, 3), the minimum distance when r = 3 and δ = 3 is upper bounded by 12. Together with (33),…”
Section: Optimal Quaternary (1 δ)-Lrcmentioning
confidence: 96%
“…According to Construction D, we can generate a 9 × 73 array code, which forms a (2, 1)-GSD code (or a (1, 3)-GSD code). This code is an optimal [657, 505, 9] q 79 locally repairable code with (7,3) i -locality when viewed as a one dimensional linear code.…”
Section: Table I a Comparison Of Mr-codes Sd-codes And Gsd-codesmentioning
confidence: 99%
“…Upper bounds on the minimum Hamming distance of locally repairable codes and constructions for them have been reported in the literature for those generalizations. For examples, the reader may refer to [3], [5], [9], [11], [13], [24], [25], [30], [31], [33], [35], [36], [42], [43], [45], [47] for (r, δ)-locality, [10], [12], [23], [37], [41], [44], [46] for (r, δ)-availability, [39] for hierarchical locality, and [28], [48] for unequal locality.…”
Section: Introductionmentioning
confidence: 99%